KIF2A regulates the development of dentate granule cells and postnatal hippocampal wiring - Noriko Homma; Ruyun Zhou; Muhammad Imran Naseer; Adeel G Chaudhary; Mohammed H Al-Qahtani; Nobutaka Hirokawa (eLife, 2018)
Kinesin super family protein 2A (KIF2A), an ATP-dependent microtubule (MT) destabilizer, regulates cell migration, axon elongation, and pruning in the developing nervous system. KIF2A mutations have recently been identified in patients with malformed cortical development. However, postnatal KIF2A is continuously expressed in the hippocampus, in which new neurons are generated throughout an individual's life in established neuronal circuits. In this study, we investigated KIF2A function in the postnatal hippocampus by using tamoxifen-inducible Kif2a conditional knockout (Kif2a-cKO) mice. Despite exhibiting no significant defects in neuronal proliferation or migration, Kif2a-cKO mice showed signs of an epileptic hippocampus. In addition to mossy fiber sprouting, the Kif2a-cKO dentate granule cells (DGCs) showed dendro-axonal conversion, leading to the growth of many aberrant overextended dendrites that eventually developed axonal properties. These results suggested that postnatal KIF2A is a key length regulator of DGC developing neurites and is involved in the establishment of precise postnatal hippocampal wiring.